Does Currency Substitution Affect Exchange Rate Volatility? - Kumamoto, Hisao; Kumamoto, Masao (International Journal of Economics and Financial Issues, 2014)
This study investigates the impacts of the degree of currency substitution on nominal exchange rate volatility in seven countries (Indonesia, the Philippines, the Czech Republic, Hungary, Poland, Argentina, and Peru). We use the Threshold ARCH model to consider the ratchet effect of currency substitution and sample periods in the 2000s, during which time the economies of the sample countries stabilized, while the U.S. dollar and euro depreciated against other major currencies following the recent global financial crisis. The presented empirical analyses show that the degree of currency substitution has significant positive effects on the conditional variance of the depreciation rate of the nominal exchange rate in most sample countries. Moreover, a shock to the depreciation rate of the nominal exchange rate has asymmetric effects on the conditional variance, depending on the sign. One possible explanation for these differential effects is the existence of the ratchet effect of currency substitution. Keywords: Currency Substitution; Exchange Rate Volatility; TARCH model JEL Classifications: E50; E52; F32; F41